Taking our country back the crafting of networked politics from Howard Dean to Barack Obama - Kreiss, Daniel (New York : Oxford University Press, 2012)
Drawing on open-ended interviews with more than 50 political staffers, fieldwork during the 2008 electoral cycle, and archival research, the book follows a group of technically skilled Internet staffers who came together on the Howard Dean campaign and created a series of innovations in campaign organization, tools, and practice.
Description based on online resource; title from home page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Internet in political campaigns -- United States -- History; Campaign management -- Technological innovations -- United States -- History; Political campaigns -- Technological innovations -- United States -- History; Political participation -- Technological innovations -- United States -- History; Presidents -- United States -- Election -- 2004 -- Technological innovations; Presidents -- United States -- Election -- 2008 -- Technological innovations; Political consultants -- United States -- History -- 21st century; Internet -- Political aspects -- United States; Digital media -- Political aspects -- United States